Model Stokastik Teori Antrean Non Poisson: Studi Kasus: Analisis Model Antrean Non-Poisson pada Pelayanan Mie Gacoan Jimbaran - Permata Sari, K. Ayu Diah; Fortuna Dewi, Ni Kadek; Dwi Octavanny, Made Ayu (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
At Mie Gacoan Jimbaran, there are two payment service units operating under a single queue line, which often leads to customer congestion during peak hours. This study aims to evaluate the most appropriate non-Poisson queueing model, assess the performance of the existing queueing system, and determine the optimal number of cashiers (servers) to enhance service efficiency at Mie Gacoan Jimbaran.The observation was conducted at Mie Gacoan Jimbaran, located in Badung, Bali, on Saturday, November 18, 2023, over a period of one hour and fifteen minutes. Based on the results of the queueing model analysis and system performance evaluation, the customer arrival rate was found to be two persons per minute, with a service rate of three persons per minute. Furthermore, the average number of customers in the system and in the queue was two individuals, respectively. The probability of the cashiers being idle was recorded at 71.28%, with an average customer waiting time of 0.7696 minutes in the queue and 1.1829 minutes within the entire system.